Al-Jahiz and the Disabled People (The Book of the Lepers, the Lames, the Blinds, and the Squitings) Study and Analysis - Abbas, Abbas (Dirasat: Human and Social Sciences, 2022)
The current study is mainly concerned to shed light on an obscured subject in our literary heritage that our contemporary culture has not yet recognized. It is the subject of the disabled people and those with special needs among ancient Arab writers and researchers, through a book that was written by Abu Uthman Amr bin Bahr Al-Jahiz (died 255 AH), under the title (The Lepers, the Lames, the Blinds and the Squintings) in which Al-Jahiz addressed these people and other disabled and people with special needs, with great care, dignity, and respect. The book speaks about their nobles, and indicates their determination and features, detailing the types of disabilities they have, and criticizing those who condemned them and denied them their rights. The study aimed to approach this book and indicate its position among other works similar to it, and then show its value in the human, social, educational and scientific aspects, through an analytical and investigative approach, in which the researcher tried to take this work as a witness and evidence of the tendency of fairness and reform towards people with disabilities, and restore to them their consideration in our ancient Arab heritage.